BIFUNCTIONAL CHIRAL AUXILIARIES-8 - UTILIZATION OF TARTARIC ACID-DERIVED AUXILIARIES IN ALDOL AND ALKYLATION REACTIONS - Davies, S; Evans, G; Pearce, S (1994)
The boron enolates of three new homochiral C2 symmetric 1,3-diacylimidazolidin-2-ones prepared from natural tartaric acid undergo highly diastereoselective aldol and alkylation reactions. Cleavage of these diastereomerically pure, adducts gives homochiral (1R,2S)-1-phenyl-2-methylpropane-1,3-diol and (2R,3R)-3-hydroxy-3-phenyl-2-methylpropanoic acid and (2S)-3-phenyl-2-methylpropan-1-ol (>92% ee). One of these auxiliaries, 4,5-dimethylimidazolidin-2-one, has the lowest effective molecular weight of any previously reported chiral auxiliary. © 1994.